(untitled) (Journal of Asian Development Studies, 2025)
This research aims at identifying the conjoint effects of m-banking social media and communication, and perceived entertainment, gamification of the service as antecedents of perceived m-banking value and the interaction of these two key cues with the two peripheral cues, perceived entertainment and gamification of the service, as an antecedent of the perceived m banking value. Such factors, in this sense, influence the future intention of the users of the m banking services. The research supports the existing findings on the Elaboration Likelihood Model (ELM). It brings forth the overall effect of rational and emotional aspects of the sustained use of m-banking by delivering ideas that can be used in the financial institutions towards developing customer experience and involvement. The study used a survey that assessed 227 m-banking customers in Pakistan, and the findings were analysed by Structural Equation Modelling (SEM). The results indicate that social media and communication are very effective in enhancing perceived value through augmenting trust and engagement, but perceived entertainment and gamification advance user experience and satisfaction. Communication appeared as the most important aspect in sustaining usage. The results show the dual role of cognitive and emotional processing in influencing m-banking user behaviour. To improve customer retention, banks should focus on developing more interactive and engaging digital features. Policymakers can promote digital financial literacy in order to boost long-term m-banking adoption.